Pemanfaatan Teknologi Elektrokoagulasi Untuk Pengolahan Limbah Cair Industri Tahu Menggunakan Elektroda Al-Al Dengan Variabel Jarak Elektroda Dan Kuat Arus - Sinaga, Hendriyanto; Amri, Idral; HS, Irdoni (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Tofu factories located in Sigunggung Subdistrict, Pekanbaru, produce 0.9 to 1 m3 of liquid waste every day, and are immediately disposed of without going through the processing process so that they pollute the environment. The analysis shows that the liquid waste is not in accordance with Permen LH No. 5 2014. In this study the electrocoagulation method was used to reduce COD, BOD, TSS and neutralize pH. By varying the current strength, electrode distance and time the results obtained as follows: (1) the effective variation of electrode distance is 2 cm current strength of 0.6 A at 60 minutes can reduce the COD concentration to 76.36%, BOD 72, 83%, TSS 85.16% and pH to 6.31. (2) effective variation of current strength is 0.6 A distance of 2 cm at 60 minutes can reduce COD concentration to 72.90%, BOD 71.69%, TSS 83.83% and pH to 6.13. The results of the research obtained are in accordance with Permen LH No.5 2014.Keywords : electrocoagulation, TSS, COD, BOD, pH